The Impact Analysis of Islamic Social Reporting Indexs on the Profitability Bank Syariah Indonesia - Fadhila Nurilaizzati; Rahmawati Khoiriyah (Universitas Muhammadiyah Surabaya, 2023)
The objective of this study is to examine the impact of Islamic Social Reporting (ISR) on the profitability of Bank Syariah Indonesia during the period of 2021-2022. Islamic Social Reporting is a manifestation of corporate responsibility towards the environment as a social concern, while adhering to Sharia principles and being answerable to Allah SWT. It aims to enhance transparency in business activities without disregarding the company's capabilities. Banking firms have traditionally relied on the Global Reporting Initiative Index (GRI) for their CSR reporting. The utilisation of the Islamic Social Reporting Index (ISR) is recommended for disclosing social performance in Sharia banking. The Islamic Social Reporting index encompasses five topics for disclosure: Finance and Investment, Products and Services, Labour, Social, Environment, and Organisational Governance. This study utilises secondary data extracted from quarterly reports available on the official website of the bank for the period of 2021-2022. The research focuses on Bank Syariah Indonesia (BSI) as its subject of study. The data processing results indicate that Islamic Social Reporting has a simultaneous impact on the profitability value. Only three parameters, labour (0.13375), social influence (0.8955), and environmental influence (0.18899), have a considerable impact on the profitability value.